Writing Instruction Tips For Automated Essay Graders How To Design an Essay for a Non-human Reader - Lamoreaux, Alise (Open textbook library., 2020)
As schools, as well as the workplace, become more automated, and remote or distance learning/working becomes the “new normal,” understanding and leveraging artificial intelligence will become a critical skill.